Parading Respectability : The cultural and moral aesthetics of the Christmas Bands Movement in the Western Cape, South Africa - Bruinders, Sylvia (African humanities series., 2019)
Parading respectability: The cultural and moral aesthetics of the Christmas Bands Movement in the Western Cape, South Africa is an intimate and incisive portrait of the Christmas Bands Movement in the Western Cape of South Africa. Drawing on her own on background as well as her extended research study period during which she became a band member and was closely involved in its day-to-day affairs, the author, Dr Sylvia Bruinders, documents this centuries-old expressive practice of ushering in the joy of Christmas through music by way of a social history of the coloured communities. In doing so, she traces the slave origins of the Christmas Bands Movement, as well as how the oppressive and segregationist injustices of both colonialism and apartheid, together with the civil liberties afforded in the South African Constitution (1996) after the country became a democracy in 1994 have shaped the movement.